The nature, causes and consequences of bullying at work: The Norwegian experience - Ståle Einarsen (Perspectives Interdisciplinaires sur le Travail et la Santé)
During the last decade, bullying at work has gradually emerged as an important issue in organizational research. Bullying at work is defined as the exposure to persistent or recurrent oppressive, offensive, abusive behavior in the workplace in which the aggressor may be a superior or a colleague. This paper presents the main contributions of one of the pioneer research groups in this field, The Bergen Bullying Group. Research findings relating to the very nature of the concept of bullying in the workplace, the causes and the consequences of the problem are presented. The paper also presents a conceptual framework for future theory development in this field.